Athletes’ Education for Their Successful Future Career After Sports—Perspective of Former Athletes and Potential Employers - Michal Varmus; Martin Mičiak; Dominika Toman; Michal Jastraban; Matej Kuljovský; Jozef Sobol; Ivo Tongel; Andrea Zahumenská (Administrative Sciences)
Although sports are a dream career for many young people, only a small percentage of athletes can make a living from this. Moreover, even elite athletes with high incomes must find other employment after sports. This justifies the development of their human capital via education valued by employers. Our article originally approaches this issue with recommendations for the effective education of athletes. The aim is to identify and analyze the key skills that former athletes use in the work environment and that help them successfully integrate into employment outside sports. Our robust scientific approach, described in the methodology, combines relevant secondary and primary data and corresponding analytical methods. The secondary data analysis identified the skills required by employers as well as the employment of former athletes in areas outside of sports. Based on quantitative primary data (questionnaire on a sample of 237 young athletes), the skills perceived as important by young athletes were revealed. The qualitative component is represented by interviews with selected former athletes and employers from the corporate environment. The main findings include the alignment of the perceived importance of certain skills by young athletes and employers. The high perceived importance of education during sports careers was supported by all stakeholders.